The 2017 Veblen-Commons Award Recipient: John F. Henry: "Brutus Is an Honorable Man". Issue 2 (3rd April 2017) - Henry, John F.
Abstract: The question I pose in this article is just why, from its egalitarian foundations, inequality first arose. There is good information regarding how inequality has been defended over the millennia, but no answer as to why, from an egalitarian ideological foundation, some began to assert a superior position, while others — the vast majority, in fact — accepted this. In this historic process that leads to the current period, it appears that those asserting a superior position are of an "honorable" nature. That is, they tend to be mass murderers, fundamentally dishonest, hypocrites, and generally anti-social. Just why is this? Why are these "honorable men" of the Brutus type at the top of the social hierarchy? While Thorstein Veblen and Karl Marx have developed cogent analyses of inequality itself, neither has explained the origins of inequality in its break and separation from the original state of equality. I propose that this is a task for institutionalists, basing their argument on Veblen's understanding of "institutions."